2018
DOI: 10.1371/journal.pone.0200124
|View full text |Cite
|
Sign up to set email alerts
|

Positive and negative adjustment in couples undergoing infertility treatment: The impact of support exchange

Abstract: BackgroundPerceived social support relates to infertility-related distress in couples undergoing assisted reproductive technology (ART) treatment. Studies examining the effect of other support types on both positive and negative adjustment among infertile couples are scarce or non-existent. Therefore, this study investigated the effects of support receipt, provision, invisibility (the discrepancy between one partner’s received and the other partner’s provided support), and equity (the discrepancy between each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 45 publications
4
26
0
9
Order By: Relevance
“…In this direction, for example, another study (Schmitt, 2003) reported that men were not significantly more avoidant than women across all culture. Finally, although no difference between men and women was found for support, a higher percentage of men were at greater risk of perceiving lack of support, partially confirming findings of another study that found lower levels of benefit from support among men (Kroemeke and Kubicka, 2018;Casu et al, 2019).…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…In this direction, for example, another study (Schmitt, 2003) reported that men were not significantly more avoidant than women across all culture. Finally, although no difference between men and women was found for support, a higher percentage of men were at greater risk of perceiving lack of support, partially confirming findings of another study that found lower levels of benefit from support among men (Kroemeke and Kubicka, 2018;Casu et al, 2019).…”
Section: Discussionsupporting
confidence: 76%
“…It is possible to surmise that the higher commitment of women in ART treatments and their greater acceptance of these treatments gives a lower weight to the medical variables directly related to the treatments, compared to other variables (Nagórska et al, 2019). These findings suggest the importance of implementing support interventions for couples which take into consideration the specific needs and fragility of each partner (Kroemeke and Kubicka, 2018) as well as focusing on maintaining and enhancing a sense of partnership. Indeed, it appears that the couple in this specific moment (i.e., the beginning of an ART treatment), can function as an important resource for partners' distress and fatigue (Molgora et al, 2019b).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations